STUDY OF LIFE EVENTS AND PREMORBID FUNCTION IN RECENT ONSET SCHIZOPHRENIA - BABU P, SURESH; KV, BALAGANESHAN; D, SIVALINGAM; S, THIRUMALAI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background and Objectives: Stressful life events preceded onset of psychosis like schizophrenia. Factors which help to identify disease at an earlier stage enable to seek early medical care. This study aims to compare occurrence of life events in subjects presenting 1st time with schizophrenia in the preceding year and to assess premorbid function of individuals. Methods: This was a case–control study with subjects attending psychiatry outpatient department for the 1st time with schizophrenia and controls from general population. After obtaining informed consent, sociodemographic data were collected along with premorbid functioning using premorbid adjustment scale (PAS), presumptive stressful life events scale (PSLES), positive and negative syndrome scale, premorbid schizoid and schizotypal assessment scale, and global assessment functioning scale (GAF). Data analysis was done using SPSS 22 software. p<0.05 was considered significant. Results: Sixty cases and 60 controls were compared. Mean age was 30.45±9.21 years, 55% were male, 56.66% were married, 68.33% were from rural background, and 81.66% were from low socioeconomic status. Mean number of stressful life events in the preceding year, PSLES score, PAS scale, Premorbid schizoid and schizotypal traits scale, and GAF scale were all significantly higher in cases. Married men showed higher stress and life events score. Conclusion: Subjects with schizophrenia experience severe stress before onset of illness and showed more premorbid social dysfunction. Married subjects experience severe stress than others. Duration of untreated illness was less in urban subjects and those with positive family history but had no correlation with severity.